Novel Porcine Epidemic Diarrhea Virus Variant with Large Genomic Deletion, South Korea - Seongjun Park; Sanghyun Kim; Daesub Song; Bongkyun Park (Emerging Infectious Diseases, 2014)
Since 1992, porcine epidemic diarrhea virus (PEDV) has been one of the most common porcine diarrhea–associated viruses in South Korea. We conducted a large-scale investigation of the incidence of PEDV in pigs with diarrhea in South Korea and consequently identified and characterized a novel PEDV variant with a large genomic deletion.